Effect of PhET simulations and YouTube videos on polytechnic students’ conceptual understanding in fluid mechanics - Jean D'Amour Iradukunda; Lakhan Lal Yadav (Institute of Advanced Engineering and Science, 2026)
Fluid mechanics is an important branch of engineering and science with various technological and scientific applications. However, students often struggle to develop a solid conceptual understanding of related concepts due to their abstract nature, which involves invisible forces and complex scientific phenomena. This study investigated the effect of physics education technology (PhET) interactive simulations combined with educational YouTube videos on students’ conceptual understanding in ten areas of fluid mechanics. Using a quasi-experimental pre-test and post-test design, 168 construction technology students from two Rwanda Polytechnic (RP) colleges were assigned to the experimental group (n=81) and the control group (n=87). The experimental group got instruction using PhET interactive simulations and YouTube videos, while the control group was taught using traditional methods. A validated test assessed students’ conceptual understanding before and after the intervention. Descriptive and inferential statistics analyses of the study show that the students in the experimental group demonstrated far enhanced conceptual understanding in different areas of fluid mechanics than those in the control group. Results using different measures (normalized learning gains and effect sizes, using different approaches) show that the experimental group gained significantly greater improvement in their level of conceptual understanding compared to that of the control group. For example, Cohen’s d for the post-test scores for the two groups was found to be 1.85; ratios of Hake’s normalized learning gains and Cohen’s d for post- and pre-test for the experimental group to the control group were respectively 2.2669 and 2.1623. Based on these findings, the study provided actionable recommendations for educational policy and practice for polytechnic colleges.